Urgensi Dan Prinsip Penerapan Pendekatan Manajemen Sumber Daya Manusia Strategis Pada Institusi Pendidikan - Binti Nasukah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2018)
To survive and thrive, educational institutions need the direction of human resources management has focused on the achievement of the long-term goals, by applying the strategic human resource management approach. This article aims to discuss the implementation of the fundamental to the human resource management (HRM) approach in educational institutions, include: the basic concepts of strategic human resource management; principles and urgency of its application in educational institutions. Through the study of literature, the results of the study show that to cope with the challenge of managing educational that an increasingly complex, it needs human resource management that not only run management functions, but also leads to the strategy to achieve the long term goals of institutions. This approach is known as the strategic human resource management. This approach became particularly urgent to implement in the educational institutions on three needs; (1) Managing human as the most important resources in the achievement of the main objectives of education; (2) Keep the accountability of institutions in the public eye; and (3) Making human resources as a competitive advantage for the institution. Its application at educational institutions require a series of principles include: understanding of the institutional environment; understanding of the development of the world of work; focus on long term goals of the institution; attention to the development of institutional personnel; and integrating human resources strategy with the strategy of the institution.